2009
DOI: 10.1186/1471-2164-10-172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomics of Daphnia symbionts

Abstract: Background: Shotgun sequences of DNA extracts from whole organisms allow a comprehensive assessment of possible symbionts. The current project makes use of four shotgun datasets from three species of the planktonic freshwater crustaceans Daphnia: one dataset from clones of D. pulex and D. pulicaria and two datasets from one clone of D. magna. We analyzed these datasets with three aims: First, we search for bacterial symbionts, which are present in all three species. Second, we search for evidence for Cyanobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 36 publications
9
89
2
Order By: Relevance
“…These features provide opportunities for identifying the influences of bacterial symbionts on Daphnia physiology at the molecular level, and these findings can be placed in an ecologically relevant framework. The microbiota of three species of Daphnia have been described, and despite the intercontinental distribution of these species, they harbor diverse but similar bacterial communities, a hint that Daphnia and their microbiota may have established a stable relationship (Qi et al, 2009). At present, the contribution of microbiota to Daphnia health is unknown and the dynamics of the interaction are uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…These features provide opportunities for identifying the influences of bacterial symbionts on Daphnia physiology at the molecular level, and these findings can be placed in an ecologically relevant framework. The microbiota of three species of Daphnia have been described, and despite the intercontinental distribution of these species, they harbor diverse but similar bacterial communities, a hint that Daphnia and their microbiota may have established a stable relationship (Qi et al, 2009). At present, the contribution of microbiota to Daphnia health is unknown and the dynamics of the interaction are uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…D. magna is a keystone species in many freshwater habitats and has been widely used as an experimental system to study ecological and evolutionary interactions (for example, Decaestecker et al, 2007;Miner et al, 2012). Daphnia is known to harbor high numbers of bacteria on the surface of its body and in its gut (Grossart et al, 2010;Eckert & Pernthaler, 2014), and Qi et al (2009) showed that several bacterial taxa are consistently found in affiliation with Daphnia, even in geographically separated populations, indicating a highly specific association between Daphnia and its microbiota. Notably, the β-proteobacterial genus Limnohabitans (Comamonadaceae) seems to be a major constituent of the Daphnia microbiota (Freese & Schink, 2011;Eckert & Pernthaler, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…High bacterial diversity, including phylotypes related to Limnohabitans, was also found when analysing prokaryotic sequences from metagenomic data of Daphnia spp. (Qi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%